2013
DOI: 10.1016/j.canlet.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer stem cells: Progress and prospects

Abstract: Epithelial stem cells are critical for tissue generation during development and for repair following injury. In both gestational and postnatal stages, the highly branched and compartmentalized organization of the lung is maintained by multiple, resident stem/progenitor cell populations that are responsible for the homeostatic maintenance and injury repair of pulmonary epithelium. Though lung epithelial injury in the absence of oncogenic mutation is more commonly expressed as chronic lung disease, lung cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 75 publications
1
55
0
3
Order By: Relevance
“…Cell surface markers were used because leukemic stem cells can reproduce the tumor after serial xenografting into immunodeficient mice. In recent years, accumulating evidence indicates the presence of CSCs in many solid tumors, including those in brain cancer [65], breast cancer [66], head and neck cancer [67 and references therein], renal cancer [68], colon cancer [69 and references therein], pancreatic cancer [70], liver cancer [71], melanoma [72], and lung cancer [73]. Although many uncertainties have developed in the last few years about the existence of CSCs, recent in vivo evidence suggests that tumors originate from CSCs [7476].…”
Section: Gastric Cancer Stem Cellsmentioning
confidence: 99%
“…Cell surface markers were used because leukemic stem cells can reproduce the tumor after serial xenografting into immunodeficient mice. In recent years, accumulating evidence indicates the presence of CSCs in many solid tumors, including those in brain cancer [65], breast cancer [66], head and neck cancer [67 and references therein], renal cancer [68], colon cancer [69 and references therein], pancreatic cancer [70], liver cancer [71], melanoma [72], and lung cancer [73]. Although many uncertainties have developed in the last few years about the existence of CSCs, recent in vivo evidence suggests that tumors originate from CSCs [7476].…”
Section: Gastric Cancer Stem Cellsmentioning
confidence: 99%
“…The regulation of CSLCs reveals substantial overlap with normal stem cells, such as the control of pluripotency, stemness, self‐renewal, differentiation and proliferation regulated by the Notch, Wingless (Wnt) and Hedgehog (Hh) pathways . These signalling pathways play vital roles in lung development and may be involved in the regulation of tumourigenesis when mutated, by causing deregulation between self‐renewal and differentiation . The division of stem cells involves the decision of cells to self‐renew or to differentiate.…”
Section: Lung Cancer Stem‐like Cellsmentioning
confidence: 99%
“…Numerous studies have reported that CSCs are responsible for heterogeneity, metastasis, drug resistance, and disease recurrence . Therefore, we also undertook sphere‐formation assays to investigate the effect of PLGF on GBC CSC properties.…”
Section: Resultsmentioning
confidence: 99%